1997
DOI: 10.1074/jbc.272.6.3238
|View full text |Cite
|
Sign up to set email alerts
|

cAMP-dependent Negative Regulation of Rat Aldehyde Dehydrogenase Class 3 Gene Expression

Abstract: We investigated the inhibitory effects of intracellular cyclic adenosine monophosphate (cAMP) levels in regulating class 3 aldehyde dehydrogenase (aldh3) gene expression using cultures of primary rat hepatocytes and transient transfection experiments with HepG2 cells. In addition to regulation by an Ah receptor-dependent mechanism, expression of many members of the Ah gene battery have been shown to be negatively regulated. As was seen for the cytochrome P450 (cyp1A1) gene, aldh3 is transcriptionally inducible… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

1999
1999
2007
2007

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 33 publications
(31 reference statements)
3
8
0
Order By: Relevance
“…This is in agreement with findings that PKC inhibitors block the AHR-mediated induction of CYP1A1 (54,(57)(58)(59)(60)(61). The mechanism of PKC action on TCDD-elicited induction is controversial with conflicting reports in the literature.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This is in agreement with findings that PKC inhibitors block the AHR-mediated induction of CYP1A1 (54,(57)(58)(59)(60)(61). The mechanism of PKC action on TCDD-elicited induction is controversial with conflicting reports in the literature.…”
Section: Discussionsupporting
confidence: 89%
“…Previously these inhibitors (3 nM calyculin A, 50 nM okadaic acid) were shown to enhance the AHR-mediated induction in mouse Hepa-1 cells by affecting a step subsequent to xenobiotic response element (XRE) binding (63). There is also a report where 20 nM okadaic acid had no effect on polycyclic aromatic hydrocarbon induction of CYP1A1 mRNA in rat primary hepatocytes (60). Phosphatase treatments of AHR/ARNT have been shown to abolish the ability of the receptor complex to bind at XRE (54,64,65).…”
Section: Discussionmentioning
confidence: 96%
“…That is, H89 inhibited ER export partially at 25 M, almost com- pletely at 50 M, and completely at 100 M (our unpublished results). In contrast, 60 M H7 (Reich and Pfeffer, 1990;Xiao et al, 1997), 120 M H8 Chuong, 1997), 9 M KT5720 (Linn et al, 1996), and 1 M chelerythrine (Herbert et al, 1990), at concentrations reported to inhibit PKA and PKC in vivo, had no detectable effect on ER export of VSVG.…”
Section: H89 Inhibits Sec13 Recruitment To Er Export Sitesmentioning
confidence: 79%
“…However, the presence of 50 M H89 in the hypotonic medium prevented altogether the appearance of GPP130 tubules ( Figure 2D). Although H89 is a potent inhibitor of PKA (Chijiwa et al, 1990), H89 did not appear to exert its inhibitory effect on hypotonically induced Golgi resident redistribution through the inhibition of PKA or conventional PKC isozymes because other selective inhibitors of PKA (120 M H8 [Lee and Chuong, 1997;Figure 4 and 9 M KT5720 [Linn et al, 1996]) and PKC (60 M H7 [Reich and Pfeffer, 1990;Xiao et al, 1997] and 1-10 M chelerythrine [Herbert et al, 1990]), all used at concentrations equal to or greater than those previously reported to be effective in HeLa cells, did not inhibit the response (our unpublished results).…”
Section: H89 Inhibits Hypotonically Induced- Bfa-induced- and Nocodmentioning
confidence: 98%
See 1 more Smart Citation